ISLAMIC PERSPECTIVES ON ETHICAL AND EDUCATIONAL THEMES IN LUIS SEPUVELDA’S ‘THE STORY OF THE SEAGULL AND THE CAT WHO TAUGHT HER TO FLY' - Nasrum, Nasrum; Nahdhiyah, Nahdhiyah; Khotimah, Husnul (Journal of Islamic Culture and Literature (JICeL), 2023)
This thesis aims to analyze didactic value. Didactic value is something that is useful in providing teaching to fellow human beings or between individuals and their environment. The novel “The Story of a Seagull and The Cat Who Taught Her to Fly” By Luis Sepulveda is a novel that contains a lot of didactic values according to the theory expressed by Diane Tillman. This study uses a qualitative approach. The data in this study are in the form of sentences or paragraphs contained in the novel. The research method used in this research is content analysis method. In this contex didacticism is reflected in various narrative elements such as characters and messages conveyed. Didactic messages taken from this novel relate to courage, self-development, and taking lessons from failure. Readers are invited to reflect on how challenges and uncertainties in life can be opportunities to learn and grow. This didactic value dominates and indicates that the author deliberately wrote the story with a specific purpose, namely to teach readers as a society that out of all the didactic values there is one most important element in life, namely the value of loyalty. Loyalty is very important to be instilled and carried out in every human being, in order to create a peace in the heart.